2018
DOI: 10.1007/s10877-018-0176-6
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic fluid content: a novel parameter for detection of pulmonary edema in parturients with preeclampsia

Abstract: Acute pulmonary oedema is a serious complication of preeclampsia. Early detection of pulmonary edema in preeclampsia would improve fluid management and would also allow earlier detection of severe cases. The aim of this work is to evaluate the ability of thoracic fluid content measured by electrical cardiometry for early detection of pulmonary edema in parturients with preeclampsia. A prospective observational study included a cohort of preeclamptic parturients. On admission, lung ultrasound score was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 19 publications
1
36
0
1
Order By: Relevance
“…In late preterm and term newborn, TFC correlated with the occurrence of respiratory distress in the first 24 h after birth [19]. Our group had recently evaluated TFC in pre-eclamptic mothers and reported that TFC could detect mothers with high risk for pulmonary edema [10]. In the current study, we evaluated TFC in another population, the critically ill patients, and found that the TFC could be a useful tool for detection of weaning failure in cardiac patients.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In late preterm and term newborn, TFC correlated with the occurrence of respiratory distress in the first 24 h after birth [19]. Our group had recently evaluated TFC in pre-eclamptic mothers and reported that TFC could detect mothers with high risk for pulmonary edema [10]. In the current study, we evaluated TFC in another population, the critically ill patients, and found that the TFC could be a useful tool for detection of weaning failure in cardiac patients.…”
Section: Discussionmentioning
confidence: 71%
“…Thoracic fluid content represents the whole (extravascular, intravascular, and intrapleural) fluid component in the thorax; thus, TFC was postulated to provide an estimation of the extravascular lung water. Our group had recently reported that TFC could detect pulmonary edema in parturients with pre-eclampsia [10]. We had also found that TFC correlated perfectly with extravascular lung water in pre-eclamptic patients [10].…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Lung ultrasound was performed by a skilled operator who was blinded to the study group. A Mindray device (DC-N6, with a phased array transducer, model P4-2, 3-6 megahertz) was used for 12-region lung ultrasound examination according to the following protocol [16]. We used the following definitions: 1) B-line: “laser-like vertical hyperechoic artefact which extends between the pleural line and the bottom of the screen, and moves with respiration”.…”
Section: Methodsmentioning
confidence: 99%